Anode foil, preparation method thereof and aluminum electrolytic capacitor

By using multi-stage reaming corrosion and medium treatment methods in the preparation process of the anode foil, the problems of poor uniformity of the anode foil and easy blockage in the prior art are solved, and the ultra-high voltage anode foil with high specific capacitance and low loss are realized, and the performance of the aluminum electrolytic capacitor is improved.

CN119889934AActive Publication Date: 2025-04-25DONGGUAN DONGYANG SOLAR SCI RES & DEV CO LTD
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202411872949.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-18
Publication Date
2025-04-25
Estimated Expiration
2044-12-18

AI Technical Summary

Technical Problem

The existing ultra-high voltage anode foil corrosion process for aluminum electrolytic capacitors has poor hole uniformity, small hole size and many support holes, which can easily cause hole blockage and affect capacitor performance.

Method used

The multi-stage reaming corrosion method is used, and the intermediate treatment is carried out between each adjacent two adjacent sections of reaming corrosion. The corrosion inhibitor in the medium treatment liquid strengthens the mass transfer and acidity of ions in the pore, improves the local environment in the pore, and expands and uniforms the tunnel holes.

Benefits of technology

It effectively improves the specific capacitance of the ultra-high voltage anode foil and reduces losses, improves the uniformity and size of the holes, reduces the risk of hole blockage, and thus improves the performance of the capacitor.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119889934A_ABST
    Figure CN119889934A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of electrode materials, and particularly relates to an anode foil, a preparation method thereof and an aluminum electrolytic capacitor. The preparation method of the anode foil comprises the steps that secondary reaming corrosion is carried out on aluminum foil subjected to primary hole forming corrosion, the secondary reaming corrosion comprises multiple sections of reaming corrosion, and intermediate treatment is carried out between every two adjacent sections of reaming corrosion. The preparation method disclosed by the invention relates to multi-section chambering corrosion, and intermediate treatment is arranged between every two adjacent sections of chambering corrosion, so that the hole size of the corrosion foil is effectively increased, and the preparation method can be used for preparing the ultrahigh-voltage anode foil with low loss and high specific volume.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of electrode materials, and in particular relates to an anode foil and a preparation method thereof, and an aluminum electrolytic capacitor. Background Art

[0002] Ultra-high voltage aluminum electrolytic capacitors have the advantages of high voltage resistance and large specific capacity, and are an important basic component in electronic engineering. Compared with medium and high voltage capacitors, ultra-high voltage aluminum electrolytic capacitors are showing a rapid development trend and have gained more and more attention in the field of inverters. Anode foil is an important component of ultra-high voltage aluminum electrolytic capacitors, and its performance has an important impact on the quality of capacitors. With the development of electronic complete systems, capacitors are facing higher requirements such as miniaturization, low profile, low impedance, and long life, which also requires the key material anode foil to have larger static capacitance and lower loss.

[0003] At present, the most mature manufacturing process of anode aluminum foil for aluminum electrolytic capacitors mainly includes an electrochemical corrosion process for the purpose of increasing the effective area of ​​aluminum foil and a chemical formation process for the purpose of growing high-quality aluminum oxide film. Among them, the electrochemical corrosion process is the basis and key to the specific capacity of the anode aluminum foil. The quality of the corrosion process technology determines whether a high specific capacity and high-performance electrode foil can be obtained. The ultra-high voltage anode foil corrosion method for aluminum electrolytic capacitors disclosed in the current prior art adopts pre-treatment-first-level DC electrochemical corrosion-first intermediate treatment-second-level DC electrochemical corrosion-second intermediate treatment-third-level DC electrochemical corrosion-post-treatment. In the actual production process, the anode corrosion foil prepared by the above process has at least poor pore uniformity, small pore size, and more branch pores, which are easy to cause pore blockage. Therefore, the existing ultra-high voltage anode foil corrosion process for aluminum electrolytic capacitors still needs to be improved. Summary of the invention

[0004] The main purpose of the present invention is to provide an anode foil and its preparation method and an aluminum electrolytic capacitor. The preparation method of the present invention involves multi-stage hole expansion corrosion, and an intermediate treatment is provided between each two adjacent stages of hole expansion corrosion, which effectively increases the hole size of the corrosion foil and can be used to prepare ultra-high voltage anode foil with low loss and high specific capacitance.

[0005] In order to achieve the above objectives, the present invention provides the following technical solutions.

[0006] In a first aspect, the present invention provides a method for preparing an anode foil, the method comprising subjecting the aluminum foil after primary pore formation corrosion to secondary pore expansion corrosion, wherein the secondary pore expansion corrosion comprises multiple stages of pore expansion corrosion, and intermediate treatment is performed between each two adjacent stages of pore expansion corrosion.

[0007] In some embodiments of the present invention, each stage of the hole expansion corrosion independently uses an acidic etching solution containing aluminum ions.

[0008] In some embodiments of the present invention, the concentration of aluminum ions in the acidic etching solution used in each stage of the hole expansion etching is independently 0.1 mol / L to 0.4 mol / L.

[0009] In some embodiments of the present invention, the acidic etching solution used in each stage of hole expansion etching independently contains nitric acid and phosphoric acid.

[0010] In some embodiments of the present invention, the acidic etching solution used in each stage of the hole expansion etching independently contains nitric acid with a concentration of 0.2 mol / L to 0.8 mol / L and phosphoric acid with a mass percentage of 0.2% to 0.8%.

[0011] In some embodiments of the present invention, each stage of hole expansion corrosion is independently carried out by direct current electrochemical corrosion, and the current density is independently 0.1A / cm 2 ~0.4A / cm 2 .

[0012] In some embodiments of the present invention, the temperature of each stage of the hole expansion corrosion is independently 50°C to 100°C.

[0013] In some embodiments of the present invention, the temperature of each stage of the hole expansion corrosion is independently 60°C to 90°C.

[0014] In some embodiments of the present invention, the temperature of each stage of the hole expansion corrosion is independently 68°C to 78°C.

[0015] In some embodiments of the present invention, the power-on time of each section of the hole expansion corrosion is independently 40s to 300s.

[0016] In some embodiments of the present invention, the power-on time of each stage of the hole expansion corrosion is independently 50s to 200s.

[0017] In some embodiments of the present invention, the power-on time of each section of the hole expansion corrosion is independently 60s to 100s.

[0018] In some embodiments of the present invention, each of the intermediate treatments independently uses a treatment solution containing a corrosion inhibitor.

[0019] In some embodiments of the present invention, the mass percentage of the corrosion inhibitor in the treatment solution of the intermediate treatment is independently 0.01% to 0.1%.

[0020] In some embodiments of the present invention, the corrosion inhibitors independently include one or more of polyvinyl alcohol, thiourea, polyethylene glycol, polyacrylic acid, polyacrylamide, polystyrene sulfonic acid, sodium polystyrene sulfonate and phosphate ester.

[0021] In some embodiments of the present invention, the treatment solutions in the intermediate treatments each independently comprise an acidic solution containing aluminum ions.

[0022] In some embodiments of the present invention, the treatment solutions in the intermediate treatments each independently contain oxalic acid.

[0023] In some embodiments of the present invention, the treatment solution of the intermediate treatment independently comprises oxalic acid at a concentration of 0.5 mol / L to 1.6 mol / L and aluminum ions at a concentration of 0.1 mol / L to 0.3 mol / L.

[0024] In some embodiments of the present invention, the treatment temperatures of the intermediate treatments are independently 50°C to 100°C.

[0025] In some embodiments of the present invention, the treatment temperatures of the intermediate treatments are each independently 50°C to 90°C.

[0026] In some embodiments of the present invention, the treatment temperatures of the intermediate treatments are each independently 50°C to 80°C.

[0027] In some embodiments of the present invention, the treatment time of the treatments is independently 10s to 500s.

[0028] In some embodiments of the present invention, the treatment time of the above-mentioned treatments is independently 10s to 400s.

[0029] In some embodiments of the present invention, the treatment time of each of the treatments is independently 20s to 300s.

[0030] In some embodiments of the present invention, the intermediate treatment is performed after each stage of the hole expansion etching.

[0031] In some embodiments of the present invention, the secondary hole expansion corrosion includes two to ten stages of hole expansion corrosion.

[0032] In some embodiments of the present invention, the secondary hole expansion corrosion includes three to eight stages of hole expansion corrosion.

[0033] In some embodiments of the present invention, the primary pore etching uses a etching solution containing aluminum ions.

[0034] In some embodiments of the present invention, the concentration of aluminum ions in the etching solution of the primary pore corrosion is 0.1 mol / L to 0.3 mol / L.

[0035] In some embodiments of the present invention, the etching solution of the primary pore corrosion is an acidic solution containing aluminum ions.

[0036] In some embodiments of the present invention, the etching solution of the primary pore corrosion contains hydrochloric acid and sulfuric acid.

[0037] In some embodiments of the present invention, the etching solution of the primary pore corrosion contains hydrochloric acid with a concentration of 0.65 mol / L to 1.0 mol / L and sulfuric acid with a concentration of 3.0 mol / L to 4.5 mol / L.

[0038] In some embodiments of the present invention, the temperature of the primary pore corrosion is 50°C to 100°C.

[0039] In some embodiments of the present invention, the temperature of the primary pore corrosion is 60-90°C.

[0040] In some embodiments of the present invention, the temperature of the primary pore corrosion is 68°C to 80°C.

[0041] In some embodiments of the present invention, the primary pore corrosion is carried out by direct current electrochemical corrosion with a current density of 0.35 A / cm 2 ~0.70A / cm 2 .

[0042] In some embodiments of the present invention, the power-on time of the primary pore corrosion is 20s to 200s.

[0043] In some embodiments of the present invention, the power-on time of the primary pore corrosion is 20s to 100s.

[0044] In some embodiments of the present invention, the power-on time of the primary pore corrosion is 40s to 80s.

[0045] In some embodiments of the present invention, the preparation method further comprises a pre-treatment performed before the primary pore etching.

[0046] In some embodiments of the present invention, the pretreatment comprises: placing the aluminum foil in an alkaline soaking solution and an acidic soaking solution in sequence.

[0047] In some embodiments of the present invention, the alkaline soaking solution contains at least one of sodium hydroxide, potassium hydroxide, sodium bicarbonate, and potassium bicarbonate.

[0048] In some embodiments of the present invention, the concentration of the alkaline soaking solution is 0.1 mol / L to 1 mol / L.

[0049] In some embodiments of the present invention, the temperature of the alkaline soaking solution is 40°C to 60°C.

[0050] In some embodiments of the present invention, the aluminum foil is immersed in the alkaline immersion solution for 20 seconds to 90 seconds.

[0051] In some embodiments of the present invention, the acidic soaking solution comprises hydrochloric acid and sulfuric acid.

[0052] In some embodiments of the present invention, the acidic soaking solution contains hydrochloric acid with a concentration of 0.65 mol / L to 1.0 mol / L and sulfuric acid with a concentration of 3.0 mol / L to 4.0 mol / L.

[0053] In some embodiments of the present invention, the temperature of the acidic soaking solution is 50°C to 85°C.

[0054] In some embodiments of the present invention, the aluminum foil is immersed in the acidic immersion solution for 40 seconds to 80 seconds.

[0055] In some embodiments of the present invention, the preparation method further includes post-treatment and drying treatment.

[0056] In some embodiments of the present invention, the post-treatment uses a treatment solution containing nitric acid.

[0057] In some embodiments of the present invention, the mass percentage of nitric acid in the treatment solution is 3% to 10%.

[0058] In some embodiments of the present invention, the post-treatment temperature is 60° C. to 80° C., and the post-treatment time is 2 min to 10 min.

[0059] In some embodiments of the present invention, the temperature of the drying treatment is 60° C. to 110° C., and the time of the drying treatment is 2 min to 10 min.

[0060] A second aspect of the present invention provides an anode foil, wherein the anode foil is prepared by the preparation method described in the first aspect.

[0061] According to a third aspect of the present invention, an aluminum electrolytic capacitor is provided. The aluminum electrolytic capacitor comprises the anode foil according to the second aspect or the anode foil prepared by the preparation method according to the first aspect.

[0062] Compared with the prior art, the present invention achieves the following technical effects:

[0063] The preparation method provided by the present invention involves multiple stages of hole expansion corrosion, and a middle treatment is provided between each two adjacent stages of hole expansion corrosion. Through the middle treatment, a large amount of aluminum ions accumulated in the tunnel hole generated during the hole expansion process can be transferred to the outside of the hole, thereby strengthening the mass transfer of ions in the hole, increasing the acidity in the hole, reducing the reaction resistance, improving the local environment in the hole, and facilitating the expansion and homogenization of the tunnel hole, thereby reducing the loss of the ultra-high voltage anode foil and increasing the specific volume of the ultra-high voltage anode foil.

[0064] The treatment liquid used in the present invention is added with a corrosion inhibitor, which can effectively inhibit the excessive dissolution and thinning of the aluminum foil surface and avoid unnecessary specific volume loss.

[0065] The above description is only an overview of the technical solution of the present invention. In order to more clearly understand the technical means of the present invention, it can be implemented according to the contents of the specification. In order to make the above and other purposes, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are listed below. BRIEF DESCRIPTION OF THE DRAWINGS

[0066] Various other advantages and benefits will become apparent to those of ordinary skill in the art by reading the detailed description of the preferred embodiments below. The accompanying drawings are only used for the purpose of illustrating the preferred embodiments and are not to be considered as limiting the present invention. In the accompanying drawings:

[0067] Figure 1 This is a process flow chart for preparing an ultra-high voltage anode foil in Example 1 of the present invention;

[0068] Figure 2 This is a process flow chart for preparing an ultra-high voltage anode foil in Example 2 of the present invention;

[0069] Figure 3 This is a process flow chart for preparing ultra-high voltage anode foil in Comparative Example 2 of the present invention;

[0070] Figure 4 This is a surface SEM image of the ultra-high voltage anode foil prepared in Example 2 of the present invention;

[0071] Figure 5 This is a surface SEM image of the ultrahigh voltage anode foil prepared in Comparative Example 2 of the present invention. DETAILED DESCRIPTION

[0072] The exemplary embodiments of the present invention will be described in more detail below with reference to specific embodiments. It should be understood that the present invention can be implemented in various forms and should not be limited by the embodiments set forth herein. On the contrary, these embodiments are provided in order to enable a more thorough understanding of the present invention and to enable the scope of the present invention to be fully communicated to those skilled in the art.

[0073] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by technicians in the technical field to which the present invention belongs; the terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the present invention; the terms "including" and "having" in the specification and claims of the present invention and the above-mentioned figure descriptions and any variations thereof are intended to cover non-exclusive inclusions.

[0074] In the description of the embodiments of the present invention, technical terms such as "first" and "second" are only used to distinguish different objects and cannot be understood as indicating or implying relative importance or implicitly indicating the number, specific order or primary and secondary relationship of the indicated technical features.

[0075] Reference to "embodiments" herein means that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment of the present invention. The appearance of the phrase in various places in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described herein may be combined with other embodiments.

[0076] In the description of the embodiments of the present invention, the term "and / or" is only a description of the association relationship of associated objects, indicating that three relationships may exist. For example, A and / or B may represent: A exists, A and B exist at the same time, and B exists. In addition, the character " / " in this document generally indicates that the associated objects before and after are in an "or" relationship.

[0077] In the description of the embodiments of the present invention, the term "multiple" refers to more than two (including two). Similarly, "multiple groups" refers to more than two groups (including two groups), and "multiple pieces" refers to more than two pieces (including two pieces).

[0078] The electrolytic corrosion process of ultra-high voltage anode foil is usually: aluminum foil-pretreatment-primary pore corrosion-secondary pore expansion corrosion-post-treatment. The main function of pretreatment is to remove the surface oil film and oxide film, adjust the surface state of aluminum foil, and promote the initial initiation of pitting. The function of primary pore corrosion is to generate a large number of tunnel holes with a certain pore diameter and depth on the surface of pretreated aluminum foil by applying direct current. The function of secondary pore expansion is to apply direct current on the basis of the tunnel holes generated by primary pores, so as to promote the pore diameter of the tunnel holes to reach the expected size, so as to avoid being blocked in the subsequent chemical formation process and reducing the specific volume. Therefore, secondary pore expansion corrosion plays a decisive role in adjusting the size of the tunnel holes, thereby affecting the specific volume and loss of the corrosion foil.

[0079] In order to control the hole size, an intermediate treatment can be added to the secondary hole expansion corrosion process. Its main function is to transfer a large amount of aluminum ions accumulated in the tunnel hole during the hole expansion process to the outside of the hole, strengthen the mass transfer of ions in the hole, increase the acidity in the hole, reduce the reaction resistance, improve the local environment in the hole, and facilitate the expansion and homogenization of the tunnel hole. For example, the ultra-high voltage anode foil corrosion method for aluminum electrolytic capacitors disclosed in the prior art adopts pre-treatment-primary DC electrochemical corrosion-primary intermediate treatment-secondary DC electrochemical corrosion-secondary intermediate treatment-third-level DC electrochemical corrosion-post-treatment. However, in the actual production process, the anode corrosion foil prepared by the above process has poor hole uniformity, small hole size, and many branch holes, which easily cause hole blockage. In addition, in the above method, the secondary intermediate treatment uses a hydrochloric acid-based mixed solution for DC electrochemical corrosion treatment, which easily introduces chloride ions into the next-level hole expansion corrosion solution, causing secondary pore formation and affecting the performance of the corrosion foil; additional DC electrochemical corrosion will also increase the production cost of the ultra-high voltage corrosion foil, resulting in a decrease in profits. Therefore, developing an efficient UHP etching method is crucial to producing high-performance UHP etching foil.

[0080] The present invention provides a method for preparing an anode foil, which comprises subjecting an aluminum foil subjected to primary pore-forming corrosion to secondary pore-expanding corrosion, wherein the secondary pore-expanding corrosion comprises multi-stage pore-expanding corrosion, and intermediate treatment is performed between each two adjacent stages of pore-expanding corrosion. In the present invention, the intermediate treatment can transfer a large amount of aluminum ions accumulated in the tunnel pores generated during the pore-expanding process to the outside of the pores, strengthen the mass transfer of ions in the pores, increase the acidity in the pores, reduce the reaction resistance, improve the local environment in the pores, facilitate the expansion and homogenization of the tunnel pores, thereby reducing the loss of the ultra-high voltage anode foil and improving the specific capacity of the ultra-high voltage anode foil.

[0081] Pre-treatment

[0082] In an embodiment of the present invention, the pre-treatment comprises placing the aluminum foil in an alkaline soaking solution and an acidic soaking solution in sequence for soaking treatment.

[0083] In some embodiments of the present invention, the concentration of the alkaline soaking solution is 0.1mol / L to 1mol / L. The concentration of the alkaline soaking solution provided by the present invention can be a value of an interval composed of any two values ​​in the above interval, for example, it can be 0.1mol / L to 0.6mol / L, or it can be 0.6mol / L to 1mol / L, and so on. The concentration of the alkaline soaking solution provided by the present invention can also be one of 0.1mol / L, 0.2mol / L, 0.3mol / L, 0.4mol / L, 0.5mol / L, 0.6mol / L, 0.7mol / L, 0.8mol / L, 0.9mol / L, 1mol / L or any value that meets the above range value.

[0084] In some embodiments of the present invention, the alkaline soaking solution contains at least one of sodium hydroxide, potassium hydroxide, sodium bicarbonate, and potassium bicarbonate.

[0085] In some embodiments of the present invention, the alkaline soaking solution may be, but is not limited to, an aqueous sodium hydroxide solution, an aqueous potassium hydroxide solution, an aqueous sodium bicarbonate solution, or an aqueous potassium bicarbonate solution.

[0086] In some embodiments of the present invention, the temperature of the alkaline soaking solution is 40° C. to 60° C. For example, the temperature of the alkaline soaking solution may be 40° C., 45° C., 50° C., 55° C., 60° C., or any value within the above range.

[0087] In some embodiments of the present invention, the immersion time of the aluminum foil in the alkaline immersion solution is 20s to 90s. The immersion time provided by the present invention can be a value of an interval composed of any two values ​​in the above range, for example, it can be 20s to 50s, or 50s to 90s, and so on. The immersion time provided by the present invention can also be one of 20s, 30s, 40s, 50s, 60s, 70s, 80s, 90s or any value that satisfies the above range.

[0088] In some embodiments of the present invention, the acidic soaking solution comprises hydrochloric acid and sulfuric acid.

[0089] In some embodiments of the present invention, the acidic soaking solution contains hydrochloric acid with a concentration of 0.65mol / L to 1.0mol / L and sulfuric acid with a concentration of 3.0mol / L to 4.0mol / L. For example, the concentration of hydrochloric acid can be one of 0.65mol / L, 0.68mol / L, 0.70mol / L, 0.72mol / L, 0.75mol / L, 0.78mol / L, 0.80mol / L, 0.82mol / L, 0.85mol / L, 0.88mol / L, 0.90mol / L, 0.92mol / L, 0.95mol / L, 0.98mol / L, 1.0mol / L or any value that satisfies the above range. The concentration of sulfuric acid can be one of 3.0mol / L, 3.2mol / L, 3.4mol / L, 3.6mol / L, 3.8mol / L, 4.0mol / L or any value that satisfies the above range.

[0090] In some embodiments of the present invention, the temperature of the acidic soaking solution is 50°C to 85°C. The temperature of the acidic soaking solution provided by the present invention can be a value of an interval composed of any two values ​​in the above range, for example, it can be 50°C to 70°C, or it can be 70°C to 85°C, and so on. The temperature of the acidic soaking solution provided by the present invention can also be one of 50°C, 55°C, 60°C, 65°C, 70°C, 75°C, 80°C, 85°C or any value that meets the above range.

[0091] In some embodiments of the present invention, the immersion time of the aluminum foil in the acidic immersion solution is 40s to 80s. The immersion time provided by the present invention can be a value of an interval consisting of any two values ​​in the above range, such as 40s to 60s, or 60s to 80s, and so on. The immersion time provided by the present invention can also be one of 40s, 50s, 60s, 70s, 80s, or any value that satisfies the above range.

[0092] In some embodiments of the present invention, the aluminum foil is immersed in an alkaline immersion solution at 40° C. to 60° C. for 20 seconds to 90 seconds, and then immersed in an acidic immersion solution at 50° C. to 85° C. for 40 seconds to 80 seconds.

[0093] First level pore corrosion

[0094] In an embodiment of the present invention, the pre-treated aluminum foil is placed in an etching solution containing aluminum ions to perform primary pitting etching.

[0095] In some embodiments of the present invention, the concentration of aluminum ions in the etching solution of the primary pore corrosion is 0.1 mol / L to 0.3 mol / L. For example, the concentration of aluminum ions in the etching solution can be one of 0.1 mol / L, 0.2 mol / L, 0.3 mol / L, or any value satisfying the above range.

[0096] In some embodiments of the present invention, the etching solution for the primary pore etching is an acidic solution containing aluminum ions.

[0097] In some embodiments of the present invention, the etching solution of the primary pore etching contains hydrochloric acid and sulfuric acid.

[0098] In some embodiments of the present invention, the etching solution of the primary pore corrosion contains hydrochloric acid with a concentration of 0.65mol / L to 1.0mol / L and sulfuric acid with a concentration of 3.0mol / L to 4.5mol / L. Exemplarily, the concentration of hydrochloric acid in the etching solution can be one of 0.65mol / L, 0.70mol / L, 0.75mol / L, 0.80mol / L, 0.85mol / L, 0.90mol / L, 0.95mol / L, 1.0mol / L or any value that meets the above range. The concentration of sulfuric acid can be one of 3.0mol / L, 3.1mol / L, 3.2mol / L, 3.3mol / L, 3.4mol / L, 3.5mol / L, 3.6mol / L, 3.7mol / L, 3.8mol / L, 3.9mol / L, 4.0mol / L, 4.1mol / L, 4.2mol / L, 4.3mol / L, 4.4mol / L, 4.5mol / L or any value satisfying the above range.

[0099] In some embodiments of the present invention, the temperature of the primary pore corrosion is 50°C to 100°C, which can be understood as the temperature of the etching solution of the primary pore corrosion is 50°C to 68°C, 68°C to 80°C, 80°C to 90°C, or 90°C to 100°C. Exemplarily, the temperature of the primary pore corrosion can be one of 50°C, 55°C, 60°C, 68°C, 70°C, 75°C, 78°C, 80°C, 85°C, 90°C, 95°C, 100°C, or any value that satisfies the above range.

[0100] In some embodiments of the present invention, the first-level pore corrosion adopts direct current electrochemical corrosion with a current density of 0.35A / cm 2 ~0.70A / cm 2 The current density of the primary pitting corrosion provided by the present invention can be a value in the interval formed by any two values ​​in the above interval, for example, it can be 0.35A / cm 2 ~0.50A / cm 2 , or 0.50A / cm 2 ~0.70A / cm 2 The current density of the primary pore corrosion provided by the present invention can also be 0.35A / cm 2 , 0.38A / cm 2 , 0.40A / cm 2 , 0.42A / cm 2 , 0.45A / cm 2 , 0.48A / cm 2 , 0.50A / cm 2 , 0.52A / cm2 , 0.55A / cm 2 、0.58A / cm 2 , 0.60A / cm 2 , 0.62A / cm 2 , 0.65A / cm 2 , 0.68A / cm 2 , 0.70A / cm 2 or any value that satisfies the above range.

[0101] In some embodiments of the present invention, the power-on time of the primary pore corrosion is 20s to 200s; for example, it can be 20s to 100s; it can also be 40s to 80s. Exemplarily, the power-on time of the primary pore corrosion can be one of 20s, 30s, 40s, 50s, 60s, 70s, 80s, 90s, 100s, 110s, 120s, 130s, 140s, 150s, 160s, 170s, 180s, 190s, 200s or any value that meets the above range.

[0102] In some embodiments of the present invention, the pre-treated aluminum foil is placed in an acidic solution containing aluminum ions at 50°C to 100°C for primary pore corrosion, and the current density of the primary pore corrosion is 0.35A / cm 2 ~0.70A / cm 2 The power-on time is 20s to 200s.

[0103] In some embodiments of the present invention, after the primary pore corrosion is completed, the aluminum foil is washed with deionized water at room temperature, and the washing time can be set according to actual needs, for example, 10 minutes.

[0104] Secondary hole expansion corrosion

[0105] In an embodiment of the present invention, the aluminum foil subjected to the primary hole-generating corrosion is subjected to the secondary hole-expanding corrosion.

[0106] It should be noted that the secondary hole expansion corrosion in the embodiment of the present invention includes multi-stage hole expansion corrosion, for example, the aluminum foil after the primary hole expansion corrosion is subjected to 2 to 10 stages of hole expansion corrosion; preferably, the secondary hole expansion corrosion includes 3 to 8 stages of hole expansion corrosion. The multi-stage hole expansion corrosion provided by the present invention can be 2 to 5 stages of hole expansion corrosion, 5 to 7 stages of hole expansion corrosion, 7 to 10 stages of hole expansion corrosion, and so on. The multi-stage hole expansion corrosion provided by the present invention can also be one of 2 stages, 3 stages, 4 stages, 5 stages, 6 stages, 7 stages, 8 stages, 9 stages, 10 stages, or any value that meets the above range value.

[0107] In some embodiments of the present invention, each stage of hole expansion etching independently uses an acidic etching solution containing aluminum ions.

[0108] In some embodiments of the present invention, the concentration of aluminum ions in the acidic etching solution used in each stage of hole expansion corrosion is independently 0.1 mol / L to 0.4 mol / L. For example, the concentration of aluminum ions in the acidic etching solution used in each stage of hole expansion corrosion can be one of 0.1 mol / L, 0.2 mol / L, 0.3 mol / L, 0.4 mol / L, or any value satisfying the above range.

[0109] In some embodiments of the present invention, the acidic etching solution used in each stage of hole expansion corrosion independently contains nitric acid and phosphoric acid.

[0110] In some embodiments of the present invention, the acidic etching solution used in each stage of hole expansion corrosion independently contains nitric acid with a concentration of 0.2mol / L to 0.8mol / L and phosphoric acid with a mass percentage of 0.2% to 0.8%. For example, the concentration of nitric acid can be one of 0.2mol / L, 0.3mol / L, 0.4mol / L, 0.5mol / L, 0.6mol / L, 0.7mol / L, 0.8mol / L, or any value that meets the above range. The mass percentage of phosphoric acid can be one of 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, or any value that meets the above range.

[0111] In some embodiments of the present invention, the temperature of each hole expansion corrosion section is independently 50°C to 100°C, which can be understood as the temperature of the acidic etching solution of each hole expansion corrosion section is independently 50°C to 68°C; can be 68°C to 78°C; can also be 60°C to 90°C, and can also be 78°C to 100°C. Exemplarily, the temperature of each hole expansion corrosion section can be one of 50°C, 55°C, 60°C, 65°C, 68°C, 70°C, 75°C, 78°C, 80°C, 85°C, 90°C, 95°C, 100°C, or any value that meets the above range.

[0112] In some embodiments of the present invention, each hole expansion corrosion is independently carried out by direct current electrochemical corrosion, and the current density is independently 0.1A / cm 2 ~0.4A / cm 2 For example, the current density of each hole expansion corrosion can be 0.1A / cm 2 , 0.2A / cm 2 , 0.3A / cm 2 , 0.4A / cm 2 or any value that satisfies the above range.

[0113] In some embodiments of the present invention, the power-on time of each hole expansion corrosion section is independently 40s to 300s. The power-on time of each hole expansion corrosion section provided by the present invention can be a value of an interval composed of any two values ​​in the above interval, for example, it can be 40s to 150s, it can be 60s to 100s, it can also be 50s to 200s, and it can also be 150s to 300s. The power-on time for each section of hole expansion corrosion provided by the present invention can also be one of 40s, 50s, 60s, 70s, 80s, 90s, 100s, 110s, 120s, 130s, 140s, 150s, 160s, 170s, 180s, 190s, 200s, 210s, 220s, 230s, 240s, 250s, 260s, 270s, 280s, 290s, 300s or any value that meets the above range.

[0114] In some embodiments of the present invention, the aluminum foil after the primary pore etching is subjected to multi-stage pore expansion etching, and each stage of pore expansion etching is independently carried out using an acidic etching solution containing aluminum ions at 50°C to 100°C, and the current density is 0.1A / cm 2 ~0.4A / cm 2 The power-on time is 40s to 300s.

[0115] Medium Processing

[0116] In some embodiments of the present invention, an intermediate treatment is carried out between each two adjacent stages of hole expansion corrosion, so that a large amount of aluminum ions accumulated in the tunnel hole generated during the hole expansion process can be transferred to the outside of the hole, thereby strengthening the mass transfer of ions in the hole, and at the same time increasing the acidity in the hole, reducing the reaction resistance, and improving the local environment in the hole, which is conducive to the expansion and homogenization of the tunnel hole, thereby reducing the loss of the ultra-high voltage anode foil and increasing the specific volume of the ultra-high voltage anode foil, and obtaining an ultra-high voltage anode foil with low loss and high specific volume.

[0117] In some embodiments of the present invention, intermediate treatment is performed after each stage of hole expansion corrosion to further reduce the loss of the ultra-high voltage anode foil and increase the specific capacity of the ultra-high voltage anode foil.

[0118] In some embodiments of the present invention, the intermediate treatment uses a treatment solution containing a corrosion inhibitor.

[0119] In some embodiments of the present invention, the mass percentage of the corrosion inhibitor in the treatment solution of the intermediate treatment is independently 0.01% to 0.1%. For example, the mass percentage of the corrosion inhibitor in the treatment solution can be independently 0.01%, 0.02%, 0.03%, 0.04%, 0.05%, 0.06%, 0.07%, 0.08%, 0.09%, 0.1% or any value that meets the above range.

[0120] In some embodiments of the present invention, the corrosion inhibitors may be independently one or more of polyvinyl alcohol, thiourea, polyethylene glycol, polyacrylic acid, polyacrylamide, polystyrene sulfonic acid, sodium polystyrene sulfonate and phosphate ester.

[0121] In some embodiments of the present invention, the treatment solutions in the intermediate treatments each independently include an acidic solution containing aluminum ions.

[0122] In some embodiments of the present invention, the treatment solutions in the intermediate treatments each independently contain oxalic acid.

[0123] In some embodiments of the present invention, the treatment solution in the treatment process independently includes oxalic acid with a concentration of 0.5mol / L to 1.6mol / L and aluminum ions with a concentration of 0.1mol / L to 0.3mol / L. Exemplarily, the concentration of oxalic acid can be independently 0.5mol / L, 0.6mol / L, 0.7mol / L, 0.8mol / L, 0.9mol / L, 1.0mol / L, 1.1mol / L, 1.2mol / L, 1.3mol / L, 1.4mol / L, 1.5mol / L, 1.6mol / L or any value satisfying the above range. The concentration of aluminum ions can be independently 0.1mol / L, 0.2mol / L, 0.3mol / L or any value satisfying the above range.

[0124] In some embodiments of the present invention, the processing temperature of the intermediate treatment is independently 50°C to 100°C, which can be understood as the processing liquid temperature of the intermediate treatment is independently 50°C to 80°C, or 50°C to 90°C, or 80°C to 100°C. For example, the processing liquid temperature can be independently one of 50°C, 55°C, 60°C, 65°C, 70°C, 75°C, 80°C, 85°C, 90°C, 95°C, 100°C or any value that meets the above range.

[0125] In some embodiments of the present invention, the processing time of the intermediate processing is independently 10s to 500s. The processing time of the intermediate processing provided by the present invention can be a value of an interval composed of any two values ​​in the above interval, for example, it can be independently 10s to 20s, 20s to 150s, 10s to 400s, 20s to 300s, 150s to 300s, or 300s to 500s. The intermediate treatment time provided by the present invention can also be independently one of 10s, 20s, 30s, 40s, 50s, 60s, 70s, 80s, 90s, 100s, 110s, 120s, 130s, 140s, 150s, 160s, 170s, 180s, 190s, 200s, 210s, 220s, 230s, 240s, 250s, 260s, 270s, 280s, 290s, 300s, 350s, 400s, 450s, 500s or any value satisfying the above range.

[0126] In some embodiments of the present invention, the aluminum foil that has undergone hole expansion corrosion is placed in a treatment solution containing a corrosion inhibitor at 50° C. to 100° C. for a treatment time of 10 s to 500 s.

[0127] Post-processing

[0128] In the embodiment of the present invention, the aluminum foil after the last intermediate treatment is post-treated. Of course, in some embodiments of the present invention, the aluminum foil after the last hole enlargement and corrosion can also be post-treated according to different process requirements.

[0129] In some embodiments of the present invention, the post-treatment uses a treatment solution containing nitric acid.

[0130] In some embodiments of the present invention, the mass percentage of nitric acid in the post-treatment solution is 3% to 10%. For example, the mass percentage of nitric acid can be one of 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, or any value satisfying the above range.

[0131] In some embodiments of the present invention, the post-treatment temperature is 60°C to 80°C, which can be understood as the post-treatment treatment liquid temperature is 60°C to 80°C. For example, the treatment liquid temperature can be one of 60°C, 65°C, 70°C, 75°C, 80°C or any value that satisfies the above range.

[0132] In some embodiments of the present invention, the post-treatment time is 2 min to 10 min. Exemplarily, the post-treatment time can be one of 2 min, 3 min, 4 min, 5 min, 6 min, 7 min, 8 min, 9 min, 10 min or any value satisfying the above range.

[0133] In an embodiment of the present invention, the aluminum foil after the last intermediate treatment is placed in a treatment solution at 60° C. to 80° C. for post-treatment, and the treatment time is 2 min to 10 min.

[0134] In some embodiments of the present invention, after the post-treatment, the aluminum foil is washed with deionized water at room temperature, and the washing time can be set according to actual needs, for example, 20 minutes.

[0135] Drying

[0136] In the embodiment of the present invention, the post-treated aluminum foil is dried.

[0137] In some embodiments of the present invention, the drying temperature is 60° C. to 110° C. For example, the drying temperature may be 60° C., 70° C., 80° C., 90° C., 100° C., 110° C., or any value within the above range.

[0138] In some embodiments of the present invention, the drying time is 2 min to 10 min. For example, the drying time can be 2 min, 3 min, 4 min, 5 min, 6 min, 7 min, 8 min, 9 min, 10 min or any value satisfying the above range.

[0139] In some embodiments of the present invention, the drying process may be performed in an oven.

[0140] The present invention also provides an anode foil, which is prepared by the above-mentioned preparation method.

[0141] The anode foil prepared by the preparation method of the present invention can be an ultra-high voltage anode foil, and the voltage range is suitable for 720V to 1000V, not limited to 850V. For example, the voltage of the anode foil can be one of 720V, 750V, 780V, 800V, 820V, 850V, 880V, 900V, 920V, 950V, 980V, 1000V or any value that meets the above range.

[0142] The present invention also provides an aluminum electrolytic capacitor, which comprises the above-mentioned anode foil or the anode foil prepared by the above-mentioned preparation method.

[0143] Unless otherwise defined, the technical terms used in the following examples have the same meanings as those generally understood by those skilled in the art to which the present invention belongs. The experimental reagents used in the following examples, unless otherwise specified, are all conventional biochemical reagents; the raw materials, instruments and equipment used in the following examples, etc., can all be purchased on the market or can be obtained by existing methods; the amounts of the experimental reagents, unless otherwise specified, are the amounts of reagents used in conventional experimental operations; the experimental methods, unless otherwise specified, are all conventional methods.

[0144] Example 1

[0145] A method for preparing an 850V anode foil, see Figure 1 As shown, the preparation method is as follows:

[0146] 1) Pretreatment: First, the aluminum foil (120 μm) was immersed in a 0.25 mol / L sodium hydroxide aqueous solution at 50° C. for 60 s, and then immersed in a mixed solution containing 1 mol / L hydrochloric acid and 3.5 mol / L sulfuric acid at 60° C. for 50 s.

[0147] 2) Primary pore corrosion: The pretreated aluminum foil was placed in a mixed solution containing 1.0 mol / L hydrochloric acid, 3.5 mol / L sulfuric acid and 0.2 mol / L aluminum ions at 70°C for primary DC pore corrosion with a current density of 0.5 A / cm 2 , the power-on time is 60s, and then the aluminum foil is washed with deionized water at room temperature for 10min.

[0148] 3) Secondary hole expansion corrosion 1: The aluminum foil after step 2) is placed in a mixed aqueous solution containing 0.5 mol / L nitric acid, 0.3 mol / L aluminum ions and 0.3% phosphoric acid at 73°C for secondary DC hole expansion corrosion at a current density of 0.25 A / cm 2 , the power-on time is 90s.

[0149] 4) Treatment 1: The aluminum foil obtained in step 3) is placed in a mixed aqueous solution containing 0.8 mol / L oxalic acid, 0.2 mol / L aluminum ions and 0.03% polyvinyl alcohol at 60° C. for chemical etching treatment for 90 seconds.

[0150] 5) Repeat the above steps 3) and 4) 4 times, respectively recorded as secondary hole expansion corrosion 2, medium treatment 2, secondary hole expansion corrosion 3, medium treatment 3, secondary hole expansion corrosion 4, medium treatment 4, secondary hole expansion corrosion 5, medium treatment 5.

[0151] 6) Post-treatment: The aluminum foil obtained in step 5) is immersed in a 5% by mass nitric acid aqueous solution at 75° C. for 3 minutes, and then the aluminum foil is washed with deionized water at room temperature for 20 minutes.

[0152] 7) Drying treatment: Place the post-treated aluminum foil in an oven at 85° C. and dry for 5 minutes.

[0153] Example 2

[0154] A method for preparing an 850V anode foil, see Figure 2 As shown, the preparation method is as follows:

[0155] 1) Pretreatment: First, the aluminum foil (120 μm) was immersed in a 0.35 mol / L sodium hydroxide aqueous solution at 40° C. for 60 s, and then immersed in a mixed solution containing 1 mol / L hydrochloric acid and 3.5 mol / L sulfuric acid at 60° C. for 50 s.

[0156] 2) Primary pore corrosion: The pretreated aluminum foil was placed in a mixed solution containing 1.0 mol / L hydrochloric acid, 3.5 mol / L sulfuric acid and 0.2 mol / L aluminum ions at 70°C for primary DC pore corrosion with a current density of 0.5 A / cm 2 , the power-on time is 60s, and then the aluminum foil is washed with deionized water at room temperature for 10min.

[0157] 3) Secondary hole expansion corrosion 1: The aluminum foil after step 2) is placed in a mixed aqueous solution containing 0.5 mol / L nitric acid, 0.3 mol / L aluminum ions and 0.3% phosphoric acid at 73°C for secondary DC hole expansion corrosion at a current density of 0.25 A / cm 2 , the power-on time is 65s.

[0158] 4) Treatment 1: The aluminum foil obtained in step 3) is placed in a mixed aqueous solution containing 0.8 mol / L oxalic acid, 0.2 mol / L aluminum ions and 0.04% polystyrene sulfonic acid at 65° C. for chemical etching for 50 seconds.

[0159] 5) Repeat the above steps 3) and 4) 6 times, respectively recorded as secondary hole expansion corrosion 2, medium treatment 2, secondary hole expansion corrosion 3, medium treatment 3, secondary hole expansion corrosion 4, medium treatment 4, secondary hole expansion corrosion 5, medium treatment 5, secondary hole expansion corrosion 6, medium treatment 6, secondary hole expansion corrosion 7, medium treatment 7.

[0160] 6) Post-treatment: The aluminum foil obtained in step 5) is immersed in a 5% by mass nitric acid aqueous solution at 75° C. for 3 minutes, and then the aluminum foil is washed with deionized water at room temperature for 20 minutes.

[0161] 7) Drying treatment: Place the post-treated aluminum foil in an oven at 85° C. and dry for 5 minutes.

[0162] Example 3

[0163] The remaining operations are the same as those in Example 2, except that:

[0164] There is no intermediate treatment 7 step, and post-treatment is directly performed after the secondary hole expansion corrosion 7.

[0165] Example 4

[0166] The remaining operations are the same as in Example 1, except that:

[0167] 4) Treatment 1: The aluminum foil obtained in step 3) is placed in a mixed aqueous solution containing 1.6 mol / L oxalic acid, 0.3 mol / L aluminum ions and 0.03% polyvinyl alcohol at 80° C. for chemical etching for 20 seconds.

[0168] Example 5

[0169] The remaining operations are the same as in Example 1, except that:

[0170] 4) Treatment 1: The aluminum foil obtained in step 3) is placed in a mixed aqueous solution containing 0.5 mol / L oxalic acid, 0.1 mol / L aluminum ions and 0.03% polyvinyl alcohol at 80° C. for chemical etching for 300 s.

[0171] Comparative Example 1

[0172] A method for preparing an 850V anode foil, the preparation method is as follows:

[0173] 1) Pretreatment: First, the aluminum foil (120 μm) was immersed in a 0.35 mol / L sodium hydroxide aqueous solution at 40° C. for 60 s, and then immersed in a mixed solution containing 1 mol / L hydrochloric acid and 3.5 mol / L sulfuric acid at 60° C. for 50 s.

[0174] 2) Primary pore corrosion: The pretreated aluminum foil was placed in a mixed solution containing 1.0 mol / L hydrochloric acid, 3.5 mol / L sulfuric acid and 0.2 mol / L aluminum ions at 70°C for primary DC pore corrosion with a current density of 0.5 A / cm 2 , the power-on time is 60s, and then the aluminum foil is washed with deionized water at room temperature for 10min.

[0175] 3) Secondary hole expansion corrosion 1: The aluminum foil after step 2) is placed in a mixed aqueous solution containing 0.5 mol / L nitric acid, 0.3 mol / L aluminum ions and 0.3% phosphoric acid at 73°C for secondary DC hole expansion corrosion at a current density of 0.25 A / cm 2 , the power-on time is 65s.

[0176] 4) Treatment 1: The aluminum foil obtained in step 3) is placed in a mixed aqueous solution containing 0.8 mol / L oxalic acid and 0.2 mol / L aluminum ions at 65° C. for chemical etching for 50 seconds.

[0177] 5) Repeat the above steps 3) and 4) 7 times.

[0178] 6) Post-treatment: The aluminum foil obtained in step 5) is immersed in a 5% by mass nitric acid aqueous solution at 75° C. for 3 minutes, and then the aluminum foil is washed with deionized water at room temperature for 20 minutes.

[0179] 7) Drying treatment: Place the post-treated aluminum foil in an oven at 85° C. and dry for 5 minutes.

[0180] Comparative Example 2

[0181] A method for preparing an 850V anode foil, see Figure 3 As shown, the preparation method is as follows:

[0182] 1) Pretreatment: First, the aluminum foil (120 μm) was immersed in a 0.35 mol / L sodium hydroxide aqueous solution at 40° C. for 60 s, and then immersed in a mixed solution containing 1 mol / L hydrochloric acid and 3.5 mol / L sulfuric acid at 60° C. for 50 s.

[0183] 2) Primary pore corrosion: The pretreated aluminum foil was placed in a mixed solution containing 1.0 mol / L hydrochloric acid, 3.5 mol / L sulfuric acid and 0.2 mol / L aluminum ions at 70°C for primary DC pore corrosion with a current density of 0.5 A / cm 2 , the power-on time is 60s, and then the aluminum foil is washed with deionized water at room temperature for 10min.

[0184] 3) Secondary hole expansion corrosion: The aluminum foil after step 2) is placed in a mixed aqueous solution containing 0.5 mol / L nitric acid, 0.3 mol / L aluminum ions and 0.3% phosphoric acid at 73°C for secondary DC hole expansion corrosion at a current density of 0.25 A / cm 2 , the power-on time is 510s.

[0185] 4) Post-treatment: The aluminum foil obtained in step 3) is immersed in a 5% by mass nitric acid aqueous solution at 75° C. for 3 minutes, and then the aluminum foil is washed with deionized water at room temperature for 20 minutes.

[0186] 5) Drying treatment: Place the post-treated aluminum foil in an oven at 85° C. and dry for 5 minutes.

[0187] Comparative Example 3

[0188] The remaining operations are the same as in Example 1, except that:

[0189] 4) Treatment 1: The aluminum foil obtained in step 3) is placed in a mixed aqueous solution containing 0.8 mol / L hydrochloric acid, 0.2 mol / L aluminum ions and 0.03% polyvinyl alcohol at 60° C. for chemical etching for 90 seconds.

[0190] Comparative Example 4

[0191] The remaining operations are the same as in Example 1, except that:

[0192] 4) Treatment 1: The aluminum foil obtained in step 3) is placed in a mixed aqueous solution containing 0.2 mol / L aluminum ions and 0.03% polyvinyl alcohol at 60° C. for chemical etching for 90 seconds.

[0193] Performance Testing

[0194] Specific capacity and loss tangent tgδ: The anode foil prepared in the embodiment and the comparative example was subjected to a 520V formation treatment in a 10% by mass boric acid solution at 90°C, and then the capacity and the loss tangent tgδ were tested using a ZX8516B electrostatic capacitance tester produced by Changzhou Zhixin Precision Electronics Co., Ltd., with a measurement accuracy of ±2%, a test frequency of 120±5HZ, a measurement voltage of less than 0.5Vrms, and a bath composition of: 1000mL of pure water, 80g of ammonium pentaborate, and a test temperature of 30±2°C.

[0195] Table 1 Performance of the ultra-high voltage anode foil prepared in the embodiments and comparative examples

[0196] Test items <![CDATA[Specific capacitance (μF / cm 2 )]]> tgδ Anode foil thickness (μm) Example 1 0.351 2.72 117 Example 2 0.358 2.58 116 Example 3 0.355 2.56 115 Example 4 0.346 2.94 117 Example 5 0.348 2.86 116 Comparative Example 1 0.331 2.65 114 Comparative Example 2 0.322 3.51 117 Comparative Example 3 0.330 3.24 116 Comparative Example 4 3.326 3.48 117

[0197] Combined with Figure 4-5 As can be seen from Table 1, adding intermediate treatment after each hole expansion corrosion is beneficial to the expansion of the etched hole diameter (such as Figure 4 and Figure 5 As shown), the specific volume of the ultra-high voltage anode foil is effectively increased and the loss is reduced; moreover, by adding corrosion inhibitors to the treatment liquid during the treatment, the excessive dissolution and thinning of the aluminum foil surface can be suppressed, avoiding unnecessary specific volume loss, which also shows that corrosion inhibitors are critical to improving the specific volume of ultra-high voltage anode foil.

[0198] The above is only a preferred specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed by the present invention should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention shall be subject to the protection scope of the claims.

Claims

1. A method for preparing an anode foil, characterized in that: The preparation method comprises performing secondary hole expansion corrosion on the aluminum foil after primary hole formation corrosion, wherein the secondary hole expansion corrosion comprises multi-stage hole expansion corrosion, and intermediate treatment is performed between each two adjacent stages of hole expansion corrosion.

2. The method for preparing an anode foil according to claim 1, characterized in that: Each stage of hole enlargement corrosion independently uses an acidic etching solution containing aluminum ions; Preferably, the concentration of aluminum ions in the acidic etching solution used in each stage of hole expansion etching is independently 0.1 mol / L to 0.4 mol / L; Preferably, the acidic etching solution used in each stage of hole expansion etching independently contains nitric acid and phosphoric acid; Preferably, the acidic etching solution used in each stage of the hole expansion etching independently contains nitric acid with a concentration of 0.2 mol / L to 0.8 mol / L and phosphoric acid with a mass percentage of 0.2% to 0.8%.

3. The method for preparing an anode foil according to claim 1, characterized in that: Each section of hole enlargement corrosion is independently carried out by direct current electrochemical corrosion, and the current density is independently 0.1A / cm 2 ~0.4A / cm 2 ; Preferably, the temperature of each stage of the hole expansion corrosion is independently 50°C to 100°C; preferably 60°C to 90°C; more preferably 68°C to 78°C; Preferably, the power-on time of each section of the hole expansion corrosion is independently 40s to 300s; preferably 50s to 200s; more preferably 60s to 100s.

4. The method for preparing an anode foil according to claim 1, characterized in that: The treatments described above are each independently treated with a treatment solution containing a corrosion inhibitor; Preferably, the mass percentage of the corrosion inhibitor in the treatment solution of the intermediate treatment is independently 0.01% to 0.1%; Preferably, the corrosion inhibitors independently include one or more of polyvinyl alcohol, thiourea, polyethylene glycol, polyacrylic acid, polyacrylamide, polystyrene sulfonic acid, sodium polystyrene sulfonate and phosphate; Preferably, the treatment solutions in the intermediate treatments each independently comprise an acidic solution containing aluminum ions. Preferably, the treatment solutions in the treatment process each independently contain oxalic acid; Preferably, the treatment solution in the intermediate treatment independently comprises oxalic acid at a concentration of 0.5 mol / L to 1.6 mol / L and aluminum ions at a concentration of 0.1 mol / L to 0.3 mol / L; Preferably, the treatment temperature of the intermediate treatment is independently 50°C to 100°C; preferably 50°C to 90°C; more preferably 50°C to 80°C; Preferably, the treatment time of each of the treatments is independently 10s to 500s; preferably 10s to 400s; more preferably 20s to 300s.

5. The method for preparing an anode foil according to claim 1, characterized in that: Performing the intermediate treatment after each section of the hole expansion corrosion; Preferably, the secondary hole expansion corrosion comprises two to ten stages of hole expansion corrosion; Preferably, the secondary hole expansion corrosion includes three to eight stages of hole expansion corrosion.

6. The method for preparing an anode foil according to claim 1, characterized in that: The first-level pore corrosion uses a corrosion solution containing aluminum ions; Preferably, the concentration of aluminum ions in the etching solution of the primary pore corrosion is 0.1 mol / L to 0.3 mol / L; Preferably, the corrosive solution of the primary pore corrosion is an acidic solution containing aluminum ions; Preferably, the corrosion solution of the primary pore corrosion contains hydrochloric acid and sulfuric acid; Preferably, the first-level pore corrosion etching solution contains hydrochloric acid with a concentration of 0.65 mol / L to 1.0 mol / L and sulfuric acid with a concentration of 3.0 mol / L to 4.5 mol / L; Preferably, the temperature of the primary pore corrosion is 50°C to 100°C; preferably 60°C to 90°C; more preferably 68°C to 80°C; Preferably, the first-level pore corrosion adopts direct current electrochemical corrosion with a current density of 0.35A / cm 2 ~0.70A / cm 2 ; Preferably, the power-on time of the primary pore corrosion is 20s to 200s; preferably 20s to 100s; more preferably 40s to 80s.

7. The method for preparing an anode foil according to claim 1, characterized in that: The preparation method further comprises a pre-treatment performed before the primary pore etching; Preferably, the pretreatment comprises: placing the aluminum foil in an alkaline soaking solution and an acidic soaking solution in sequence; Preferably, the alkaline soaking solution contains at least one of sodium hydroxide, potassium hydroxide, sodium bicarbonate, and potassium bicarbonate; Preferably, the concentration of the alkaline soaking solution is 0.1 mol / L to 1 mol / L; Preferably, the temperature of the alkaline soaking solution is 40°C to 60°C; Preferably, the aluminum foil is immersed in the alkaline immersion solution for 20s to 90s; Preferably, the acidic soaking solution contains hydrochloric acid and sulfuric acid; Preferably, the acidic soaking solution contains hydrochloric acid with a concentration of 0.65 mol / L to 1.0 mol / L and sulfuric acid with a concentration of 3.0 mol / L to 4.0 mol / L; Preferably, the temperature of the acidic soaking solution is 50°C to 85°C; Preferably, the aluminum foil is immersed in the acidic immersion solution for 40 seconds to 80 seconds.

8. The method for preparing an anode foil according to claim 1, characterized in that: The preparation method also includes post-treatment and drying treatment; Preferably, the post-treatment uses a treatment solution containing nitric acid; Preferably, the mass percentage of nitric acid in the treatment solution is 3% to 10%; Preferably, the post-treatment temperature is 60°C to 80°C, and the post-treatment time is 2min to 10min; Preferably, the temperature of the drying treatment is 60° C. to 110° C., and the time of the drying treatment is 2 min to 10 min.

9. An anode foil, characterized in that: The anode foil is prepared by the preparation method according to any one of claims 1 to 8.

10. An aluminum electrolytic capacitor, characterized in that: The aluminum electrolytic capacitor comprises the anode foil according to claim 9 or the anode foil prepared by the preparation method according to any one of claims 1 to 8.

Citation Information

Patent Citations

  • Ultrahigh voltage anode foil corrosion method for aluminum electrolytic capacitor

    CN102983008A

  • Stepped non-sinusoidal waveform frequency conversion corrosion method for low-voltage anode aluminum foil used for electrolytic capacitor

    CN105006367A

  • Method for manufacturing phosphorus-free reaming aluminum electrolytic capacitor electrode foil

    CN110289171A

  • Method for corroding electrode foil for aluminum electrolysis capacitor, and electrode foil

    CN112038101A

  • Process method for treating and thinning middle-high voltage anode aluminum foil

    CN112863879A